Estimación de parámetros genéticos para producción de leche en búfalas (Bubalus bubalis) de segundo y tercer parto mediante modelos de regresión aleatoria (2015)
ABSTRACT: Genetic parameters and covariance functions for test day (TD) of milk yield in buffaloes in Colombia by random regression models (MRA) with orthogonal Legendre polynomials (LP) were estimated. Records of 16738 and 14275 TD of 2284 and 1987 animals of second (L2) and third (L3) lactation were used, respectively. The average lactation curve of the population fixed effect and additive genetic and permanent environment random effect were estimated by MRA using third to sixth LP order and the residuals variances were modeled using homogeneous and heterogeneous structures. The best model was obtained with a third, fifth and fourth LP order for fixed curve of the population, genetic and permanent environment effects, respectively and fourth heterogeneous residual variances for L2 and L3 lactation. The estimated heritabilities varied between 0.05 and 0.24. The estimates of genetic correlations were highest between adjacent days. It is concluded that the application of MRA in L2 and L3 lactation described properly genetic parameters for milk yield in buffaloes.